THE TRAINING OF DIGITAL COMIC “CANDI SEWU” FOR STUDENTS WITH SPECIAL NEEDS AT SLB 1 BANTUL - Atmaja Septa Miyosa (LPPM Institut Desain dan Bisnis Bali, 2023)
Responding to the digital comic competition for students with special needs at the national level, which is nicknamed the FLS2N, it is necessary to provide guidance in the form of training for contest participants in the field of digital comics. The training was held for six days, from 19 to 24 June 2023 in Yogyakarta. Participants have special needs, namely deafness, so the training method used is direct instruction and demonstration techniques. The direct instruction method is carried out with the help of the participant's companion with sign language. The demonstration technique is carried out by showing the process of making comics from sketching to coloring using the same equipment as the equipment used by the participants. The training process uses a laptop, Photoshop and pen tablet. The comic theme is folklore that has elements of humor and motivation. The result of the training is a comic about the folklore of Candi Sewu which is narrated in parody, which as a whole is painted using digital techniques. The story of Sewu Temple, which in convention is the story of an unfinished temple project, however the story in this comic is told differently, that is, the Sewu temple project can be completed completely.